2019
DOI: 10.1093/jamia/ocz189
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences for visualization of longitudinal patient-reported outcomes data

Abstract: Objective The study sought to design symptom reports of longitudinal patient-reported outcomes data that are understandable and meaningful to end users. Materials and Methods We completed a 2-phase iterative design and evaluation process. In phase I, we developed symptom reports and refined them according to expert input. End users then completed a survey containing demographics, a measure of health literacy, and items to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 76 publications
0
19
1
Order By: Relevance
“…Many studies focused on the creation and evaluation of customized data displays. These customized data displays also focused on a diverse set of application areas, including integrated dashboards [ 10 , 61 , 124 ], critical care displays [ 96 ], opioid management [ 123 ], plan of care tools [ 125 ], and patient-focused communication [ 11 , 55 , 98 ]. A smaller number of studies addressed non-EHR integrated information systems [ 9 , 65 , 68 , 83 , 112 , 120 ], and EHR training design [ 46 , 59 , 135 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies focused on the creation and evaluation of customized data displays. These customized data displays also focused on a diverse set of application areas, including integrated dashboards [ 10 , 61 , 124 ], critical care displays [ 96 ], opioid management [ 123 ], plan of care tools [ 125 ], and patient-focused communication [ 11 , 55 , 98 ]. A smaller number of studies addressed non-EHR integrated information systems [ 9 , 65 , 68 , 83 , 112 , 120 ], and EHR training design [ 46 , 59 , 135 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mobile apps [105,113] [17,29,69,70,81,87,91,99,118,119,126,129,33,130,132,142, 34,36,37,49,50,53,67] [ 10,11,92,96,98,[123][124][125][50][51][52]55,61,66,72,84] [ 13,15,47,54,[56][57][58]63,75,85,108,110,23,[115][116][117]121,122,127,131,[25][26][27]30,35,40,41] Fig. 2 Relative weighting of HF/E outcomes by domain [1].…”
Section: Customized Data Displaysmentioning
confidence: 99%
“…Two of the four selected best papers fell into this category; the Reading-Turchioe et al paper [ 3 ] focused on presenting healthcare data to patients while the Tschandl et al [ 4 ] paper focused on presenting results from AI models for diagnosing skin lesions. In addition, Stonbraker et al [ 5 ] designed a thorough study of data presentations of longitudinal patient reported outcomes to determine which ones promoted the best comprehension. They found that patients interpreted the visualizations very literally and that while they preferred bar charts with emojis, they could confuse the meaning of the emojis if they were not precisely tailored to the symptom or outcome they were representing.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, by adding features such as symptom emojis, children and adolescents are able to easily use a familiar and common communication tool. Emojis, expressive symbols used in everyday life, may offer a new way to communicate the symptom experience (Stonbraker et al, 2019), particularly for children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Emojis are pictographs that represent emotions, feelings, and moods through facial expressions (Jaeger et al, 2017; Kralj Novak et al, 2015). They are likable, popular, and easy-to-understand communication tools (Kralj Novak et al, 2015; Stonbraker et al, 2019; Thompson et al, 2018) and provide an easy way for children and adolescents to express themselves. Current research shows that emojis can be especially useful for expressing symptoms (Thompson et al, 2018), and efforts are underway to demonstrate that emojis are a valid and reliable measure of patient well-being (Jaeger et al, 2017; Tandyonomanu & Tsuroyya, 2018).…”
Section: Phase 2: App Redesignmentioning
confidence: 99%